POLICY IMPLEMENTATION OF IMMIGRATION CLASS 1 TPI SURABAYA IN MONITORING FOREIGN NATIONALS FOR RESIDENCE PERMIT VIOLATIONS ON VISITOR VISA SUBJECTS FROM 2019-2022POLICY IMPLEMENTATION OF IMMIGRATION CLASS 1 TPI SURABAYA IN MONITORING FOREIGN NATIONALS FOR RESIDENCE PERMIT VIOLATIONS ON VISITOR VISA SUBJECTS FROM 2019-2022 - Fadhlan Ginting S; Fedianty Augustinah; Widyawati Widyawati; Sri Kamariyah (DIA: Jurnal Administrasi Publik, 2025)
This research examines the implementation of the residency permit monitoring policy by Immigration Class 1 TPI Surabaya regarding violations of residency permits for visit visa subjects during the period of 2019-2022. The policy aims to enforce regulations concerning the presence of foreign nationals in Indonesia. However, its implementation faces various challenges, particularly in terms of communication, bureaucratic structure, resources, and the disposition or attitude of policy implementers. This study aims to evaluate the effectiveness of the policy and identify areas requiring improvement to enhance monitoring performance. This study employs a qualitative method with a descriptive approach. Data were collected through in-depth interviews with officers from Immigration Class 1 TPI Surabaya and an analysis of documents related to the policy and its implementation. The findings reveal that the effectiveness of inter-unit communication in conveying policy information only reaches 75%, leading to delays in information dissemination and field coordination. Additionally, a rigid and inefficient bureaucratic structure causes 70% of monitoring processes to experience obstacles. Resource limitations, both in terms of personnel and technological facilities, also hinder implementation, with only 65% of required resources available. The implementers' disposition, achieving only about 68%, indicates a lack of commitment and consistency in executing the policy. The conclusion of this research is that the implementation of the residency permit monitoring policy at Immigration Class 1 TPI Surabaya requires significant improvements in communication, bureaucratic structure, resources, and implementers' disposition. Recommendations include increasing personnel numbers, updating monitoring technology, and conducting regular training to enhance the attitude and competence of policy implementers.